Numerical study of dynamic response of different fuels jet diffusion flame to standing waves in a longitudinal tube - Jin, Xiao (2018)
In this work, the dynamic response of jet diffusion flame of burning hydrogen and propane respectively in a longitudinal tube to acoustic standing waves produced from a loudspeaker are studied. For this, 2-D numerical simulations are conducted by using FLUENT to investigate the interaction of acoustics-flow-flame. And acoustic fluctuations are generated by using User Defined Function (UDF). The numerical model is validated first by comparing the numerical results with the experimental measurements. To gain insight on the difference between combustion flame of propane and hydrogen, 19 monitors points are set to gain the data of their distribution of pressure, temperature, mass fraction of H2O and velocity in the longitudinal tube. The result indicates that their difference concentrates on the pressure and mass fraction of H2O. The phase diagrams of pressure and velocity show that the hydrogen combustion flame is more stable than propane, which is beneficial for combustion systems.